Clinical observation and risk assessment after splenectomy in hepatolenticular degeneration patients associated with hypersplenism - Zhang, Wanzong; Yu, Qingsheng; Peng, Hui; Zheng, Zhou; Zhou, Fuhai (Frontiers in Surgery, 2022)
Background Both hepatolenticular degeneration (HLD) and viral hepatitis B (HBV) can cause hypersplenism, but whether splenectomy is needed or can be performed in HLD patients associated with hypersplenism is still controversial. At present, HLD combined with hypersplenism has not been listed as the indication of splenectomy. Objective To investigate the efficacy, risks and postoperative complications of splenectomy in HLD patients associated with hypersplenism. Methods We retrospectively analyzed the clinical data of 180 HLD patients with hypersplenism who underwent splenectomy in the Department of General Surgery, First Affiliated Hospital of Anhui University of Traditional Chinese Medicine from January 2001 to December 2015. To evaluated the efficacy of splenectomy, the hemogram of white blood cells (WBC), red blood cells (RBC), platelets (PLT), and the liver function indexes including alanine aminotransferase (ALT), aspartate aminotransferase (AST) and total bilirubin (TB) were recorded before surgery and 1, 3, 5, 7, and 14 days after surgery. Besides, the clinical data of 142 HBV patients with hypersplenism who underwent splenectomy over the same period were also recorded and compared with that of HLD patients. In particular, aiming to assess the risks of splenectomy in HLD, we also compared postoperative complications and 36-month mortality between two groups. Result The level of WBC, RBC and PLT were all elevated after splenectomy in both HLD group and HBV group. However, there was no significant difference in the variation of hemogram after splenectomy between two groups (P ＞0.05). Similarly, the variation of liver function indexes showed no statistical difference between two groups. In terms of the incidence of postoperative complications including abdominal bleeding, pancreatic leakage, PVST, incision infection, lung infection and 36-month mortality, there were no significant difference between two groups. Conclusions After splenectomy, the hemogram as well as liver function in HLD group improved a lot and showed a consistent tendency with that in HBV group. Meanwhile, compared to HBV group, there was no significant difference in the incidence of postoperative complications in HLD group. All these results indicates that splenectomy in HLD patients combined with hypersplenism is completely feasible and effective.